Vitamin D3 Protects against Diabetic Retinopathy by Inhibiting High-Glucose-Induced Activation of the ROS/TXNIP/NLRP3 Inflammasome Pathway - Li Lu; Qianyi Lu; Wei Chen; Jingwen Li; Chunxia Li; Zhi Zheng (Journal of Diabetes Research)
Purpose. This study aimed to evaluate the mechanisms underlying the effects of 1,25-dihydroxyvitamin D (vitamin D3) on diabetes-induced retinal vascular damage and retinal vascular endothelial cell apoptosis. Methods. Diabetic and control rats were randomly assigned to receive vitamin D3 or vehicle for 6 months. Additionally, human retinal microvascular endothelial cells (HRMECs) were incubated in normal or high-glucose medium with or without vitamin D3. Morphological changes in retinal tissues and retinal vascular permeability were examined, and cellular apoptosis was detected by fluorescence staining. Intracellular reactive oxygen species (ROS) levels were determined using fluorescent probes. Proteins were examined by Western blotting. Results. Vitamin D3 significantly downregulated intracellular ROS and inhibited TRX-interacting protein (TXNIP)/NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome pathway activation. Additionally, vitamin D3 reduced vascular endothelial growth factor (VEGF) expression and the Bax/Bcl-2 ratio. These changes were associated with retinal recovery and with decreases in retinal vascular permeability and retinal capillary cell apoptosis. Conclusions. Vitamin D3 decreases diabetes-induced ROS and exerts protective effects against retinal vascular damage and cell apoptosis in association with inhibition of the ROS/TXNIP/NLRP3 inflammasome pathway. Understanding the mechanisms of action of vitamin D3 has important implications for preventing and treating inflammatory-related illnesses such as diabetic retinopathy.